CONTRIBUŢII LA CERCETAREA ALGOFLOREI r. BÂC ÎN LIMITELE mun. CHIŞINĂU - Bulimaga, Constantin; Grabco, Nadejda; Molgâldea, Vladimir; Negara, Corina (CEP USM, 2010)
The algal flora study of the river Bîck on the Chisinau city shows the presence of 50 species, including the spectrum of biological species: Bacillariophyta – 21, Chlorophyta – 16, Euglenophyta – 7, Cyanophyta – 5 and Pyrophyta – 1. The saprobiological spectrum of indicator species of saprobities includes a total of 32 species with predomination of β-mezasaprobic (21 species)
Keywords: algoflorai r. Bâc